Multisource energy harvesting using (Ba,Ca)(Zr,Ti)O3 oscillating under temperature gradient - Yamamoto, Ryota; Schwarz, Michael; Martin, Alexander; Mergheim, Julia; Kakimoto, Ken ichi (Journal of the American Ceramic Society, 2024)
The concept of multisource energy harvesting has attracted attention in order to harvest multiple types of energy in a single material. In this work, Pb-free (Ba,Ca)(Zr,Ti)O3 (BCZT) ceramics were used to investigate a combination of piezoelectric and pyroelectric energy harvesting behavior. The temperature dependence of the permittivity and the pyroelectric coefficient was measured, and the pyroelectric properties of BCZT were expected to improve near its orthorhombic–tetragonal phase transition temperature TO–T (∼40°C). The output voltage and current were measured using a BCZT plate, where the BCZT was oscillated under a temperature gradient to apply mechanical stress and temperature fluctuation simultaneously. The measured output voltage from the combined piezo- and pyroelectric contributions at a frequency of 2 Hz and with a load resistance of 10 MΩ was 1.4 times higher than the sole piezoelectric output voltage. The resulting combined output voltage was confirmed by finite element simulation.
CRIS-Team Scopus Importer:2024-12-06
Keywords: energy harvesting; finite element analysis; piezoelectric materials/properties; pyroelectricity

Node Based Non-invasive Form Finding Revisited-The Challenge of Remeshing - Caspari, Michael; Schwarz, Michael; Steinmann, Paul (Springer International Publishing, 2022)
In the numerical simulation of forming processes, the material configuration describes the semi-finished part, whereas the spatial configuration represents the finished part. In order to keep the subsequent finishing steps of the manufactured component to a minimum, the aim is to produce the finished part within small geometric tolerances. Thereby, a predefined target configuration defines the optimal shape of the part. Here, non-invasive form finding is designed to minimize the difference between the spatial configuration and the target configuration during an iterative procedure. The material configuration, ergo the shape of the semi-finished part, is successively optimized. Starting point of the optimization is the computation of the difference between the computed spatial and the target configuration. The present paper deals with the computation of this difference. Special attention is paid to the variable number of design parameters. The varying number of design parameters is due to the use of re-meshing within the FE-simulation.
CRIS-Team Scopus Importer:2024-12-16